First unambiguous evidence of Multituberculata from the Late Cretaceous of South America - Gelfo, Javier Nicolás (2025)
We report a left upper first molar of a multituberculate mammal, from the Upper Cretaceous La Colonia Formation, Chubut Province, Argentina, which is here assigned to Notopolytheles joelis gen. et sp. nov. (Cimolodonta,?Neoplagiaulacidae). Multituberculates have been previously reported from Gondwanan land masses, but to date, only records from Australia, Madagascar, and India have been taxonomically undisputed. In South America, all previous assignments were debated or later referred to Gondwanatheria. These records include isolated molars attributed to Ferugliotheriidae and Argentodites coloniensis, only known from a plagiaulacoid premolar and originally assigned to the ?Cimolodonta. Since no molar with definitive multituberculate features could ever be found in the Upper Cretaceous of Patagonia, A. coloniensis was considered a junior synonym of the ferugliotheriid Ferugliotherium windhauseni. Notopolytheles joelis gen. et sp. nov. displays a typical multituberculate molar configuration of three rows of tetrahedral cups, with a cusp formula of 7B:8M:4L similar to Neoplagiaulacidae. The lower position of the buccal cusp row supported by a single large labial root suggest a high level of endemism. This finding provides strong and renewed support for the hypothesis that ferugliotheriids lack a plagiaulacoid p4 and that Argentodites coloniensis is indeed a multituberculate.